THOR’S JOURNEY AS A HERO IN THOR: RAGNAROK FILM (2017) - Rahman, Arif; Sili, Surya; M., Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
The hero’s journey is the journey that has to be passed by the hero in their adventure to finish their mission. This research was aimed to explain about Thor’s journey as a hero to save his people in Asgard of Thor: Ragnarok (2017) film. This research used Joseph Campbell’s theory of hero’s journey to explain about Thor’s journey as a hero in the film. This research was a qualitative research. The data used in this research came from the scenes and script (dialogues) related to Thor’s journey as a hero. The result of this research showed that Thor passed the three stages in hero’s journey. Thor passed all the steps in the first stage (Departure) which were Call of Adventure, Refusal of the Call, and Crossing the First Threshold. He also passed all the steps of the second stage (Initiation) such as the Road of Trials, Atonement with The Father, Apotheosis and The Ultimate Boon. In the third stage (Return), Thor was not able to pass all the steps. He passed three steps out of five which were the Resque from Without, Master of the Two Worlds, and Freedom to Live